2022
DOI: 10.1101/2022.08.26.505392
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Introgression between highly divergent fungal sister species

Abstract: To understand how species evolve and adapt to changing environments, it is important to study gene flow and introgression due to their influence on speciation and radiation events. Here, we apply a novel experimental system for investigating these mechanisms using natural populations. The system is based on two fungal sister species with morphological and ecological similarities occurring in overlapping habitats. We examined introgression between these species by conducting whole genome sequencing of individua… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…In addition, Treemix identified introgression into the East Asian lineages from an unsampled lineage related to the outgroup T. fuscoviolaceum . Kinneberg et al 64 found support for ancient introgression between T. abietinum and T. fuscoviolaceum , and it is conceivable that introgressed genes from the T. fuscoviolaceum clade have spread into North America A and B through populations in East Asia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Treemix identified introgression into the East Asian lineages from an unsampled lineage related to the outgroup T. fuscoviolaceum . Kinneberg et al 64 found support for ancient introgression between T. abietinum and T. fuscoviolaceum , and it is conceivable that introgressed genes from the T. fuscoviolaceum clade have spread into North America A and B through populations in East Asia.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Treemix identified introgression into the East Asian lineages from an unsampled lineage related to the outgroup T. fuscoviolaceum. Kinneberg et al 64 found support for ancient introgression between T. abietinum and T. fuscoviolaceum, and it is conceivable that introgressed genes from the T. fuscoviolaceum clade have spread into North America A and B through populations in East Asia. We applied demographic modelling with Fastsimcoal2 65 to explicitly test for secondary contact between the reproductively isolated North America A and B, and to estimate divergence time between the major lineages (table1).…”
Section: Relating Reproductive Barriers To Secondary Contactmentioning
confidence: 99%